Vitamin B12 Deficiency due to Chlorofluorocarbon: A Case Report - Hemlata Bhaskar; Rekha Chaudhary (Case Reports in Medicine)
Background. Vitamin B12 is vital for optimal functioning of various organ systems but more importantly the central nervous system and the hematological system. Deficiency of vitamin B12 clinically manifests as excessive daytime fatigue, memory difficulties, encephalopathy, myelopathy, peripheral neuropathy, and optic neuropathy. In occupational medicine, vitamin B12 deficiency has been reported with exposure to nitrous oxide in health care workers. However, not much is known about exposure to Freons in other industries and vitamin B12 deficiency. Aim. We are reporting a case of vitamin B12 deficiency in the setting of exposure to chlorofluorocarbon (CFC) gases. Case Report. A 55-year-old male refrigerator mechanic experienced recurrent visual symptoms, which included diplopia and blurring. A complete workup was done and was significant of vitamin B12 deficiency. However, his B12 levels were refractory to supplementation. Appropriate precautions at workplace improved patient's symptoms and were associated with significant improvement in B12 levels. Conclusion. To the best of our knowledge, this is the first reported case of vitamin B12 deficiency (that remains refractory to supplementation) in the setting of exposure to Freon gases.